Pengaruh Green Marketing Mix terhadap Keputusan Pembelian Susu Oatside sebagai Produk Hijau pada Mahasiswa di Kota Bandung - Adawiya, Alifiya Dipta; Kastaman, Roni; Syahmurman, Faizal (Universitas Galuh, 2025)
In the last few decades, global public awareness of preserving the environment has increased. Young consumers are also increasingly concerned about the environment by purchasing environmentally friendly products, such as plant-based milk. This research aims to see the influence of the green marketing mix on purchasing decisions for Oatside plant-based milk among students in Bandung. The independent variables consist of green product (X1), green price (X2), green place (X3), and green promotion (X4) with purchasing decisions (Y) as the dependent variable. Respondents consisted of 100 students in Bandung City. The method used is descriptive with multiple linear regression analysis. The research results show that green product, green price, green place, and green promotion simultaneously have a significant influence on purchasing decisions using the f-test. Partially using the t-test, the green price variable (X2) has the most dominant influence on purchasing decisions.